In-bore transrectal MRI-guided prostate biopsies: Are there risk factors for complications?. Issue 12 (December 2016) - Meier-Schroers, Michael; Homsi, Rami; Kukuk, Guido; Wolter, Karsten; Decker, Georges; Fischer, Stefan; Marx, Christian; Schmeel, Frederic Carsten; Block, Wolfgang; Sprinkart, Alois Martin; Traeber, Frank; Schild, Hans Heinz; et al.
Abstract: Purpose: To systematically analyze risk factors for complications of in-bore transrectal MRI-guided prostate biopsies (MRGB). Materials and methods: 90 patients, who were scheduled for MRGB were included for this study. Exclusion criteria were coagulation disorders, therapy with anticoagulant drugs, and acute infections of the urinary and the lower gastrointestinal tract. Directly after, one week and one year after the biopsy, we assessed biopsy related complications (e.g. hemorrhages or signs of prostatitis). Differences between patients with and without complications were analyzed regarding possible risk factors: age, prostate volume, number of taken samples, biopsy duration, biopsy of more than one lesion, diabetes, arterial hypertension, hemorrhoids, benign prostate hyperplasia, carcinoma or prostatitis (according to histopathological analysis), and lesion localization. Complications were classified according to the Clavien-Dindo classification. Results: We observed 15 grade I complications in 90 biopsies (16.7%) with slight hematuria in 9 cases (10%), minor vasovagal reactions in 4 cases (4.4%), and urinary retention and positioning-related facial dysesthesia in 1 case each (1.1%). One patient showed acute prostatitis requiring antibiotics as the only grade II complication (1.1%). There were no adverse events that occurred later than one week. Complications grade III or higher such as pelvic abscesses, urosepsis or severe hemorrhages were not seen. There were no significant associations between the assessed risk factors and biopsy-related complications. Conclusion: In-bore transrectal MRI-guided prostate biopsies can be considered safe procedures in the diagnosis of prostate cancer with very low complication rates. There seem to be no risk factors for complications.